2011
DOI: 10.2215/cjn.03220410
|View full text |Cite
|
Sign up to set email alerts
|

Donor Phosphorus Levels and Recipient Outcomes in Living-Donor Kidney Transplantation

Abstract: SummaryBackground and objectives In living-donor kidney transplantation, various donor factors, including gender, age, and baseline kidney function, predict allograft function and recipient outcomes after transplantation. Because higher phosphorus is predictive of vascular injury in healthy adults, the effect of donor phosphorus levels on recipient renal function after transplantation was investigated.Design, setting, participants, and measurements Phosphorus levels in 241 living donors were analyzed from a 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several studies have shown associations between serum phosphorus levels and decline in renal function in pediatric and adult patients with CKD (8-10), and graft failure in adult renal transplant patients (11,(13)(14)(15). Serum phosphorus levels above recommended targets were associated with a higher risk of graft loss, even after adjustment for eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown associations between serum phosphorus levels and decline in renal function in pediatric and adult patients with CKD (8-10), and graft failure in adult renal transplant patients (11,(13)(14)(15). Serum phosphorus levels above recommended targets were associated with a higher risk of graft loss, even after adjustment for eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in children (8) and adult patients with early (9) or advanced CKD (10), serum phosphorus was independently associated with a decline in renal function. Moreover, donor (11), pretransplant (12,13), and post-transplant (14-16) mineral levels have been associated with graft failure in adult renal graft recipients. Information on mineral metabolism in pediatric graft recipients mainly originates from small single-center studies with relatively short follow-up time (5,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pretransplant recipients' serum phosphorus level on transplant outcomes is un-clear; however, a recent study showed in living kidney donor transplants that a higher donor phosphorus level was an independent risk factor for early allograft dysfunction (24). We sought to examine the association of pretransplant serum phosphorus levels with all-cause and CVD mortality, graft failure, and delayed graft function (DGF) in a U.S.-based renal transplant population and we hypothesized that higher phosphorus levels are incrementally associated with poor graft and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…59 Chang and associates indicated that DGF or slow graft function after transplant is independently correlated with higher donor phosphorus levels. 60 Clinical issues like the duration between radiologic renal observation and transplant also modulate the risk of DGF incidence. Tutal and associates reported that DGF was observed in a greater number of patients undergoing early transplant (≤ 20 d; n = 42) than late transplant (≥ 20 d; n = 38) after renal angiography (22.0% vs 2.6%; P = .009).…”
Section: Other Risk Factorsmentioning
confidence: 99%